CHARACTERIZATION OF LEACHATE FROM PANCHANG BEDENA LANDFILL, BATANG PADANG LANDFILL AND MATANG LANDFILL: A COMPARATIVE STUDY - M.S., Nor Nazrieza; M.Y., Siti Rohana; K., Subramaniam; H., Hazilia; A., Amir Herberd (Malaysian Journal of Science, 2015)
A Landfill is the main disposal method of solid waste in Malaysia but this creates issues due to its leachate generation. Improper leachate treatment pollutes the environment and is harmful to human health. This study aims to determine the characteristics of landfill leachate from three landfills sites that differs in age and types; Panchang Bedena Landfill (PBL), Batang Padang Landfill (BPL) and Matang Landfill (ML). The parameters tested in this study include pH, temperature, suspended solid (SS), chromium hexavalent, BOD5, COD, copper, lead and cadmium. Analysis was carried out with standard methods using HANNA HI 9828 Portable Multiparameter, atomic absorption spectrophotometer and portable spectrophotometer, HACH DR2800. The mean values of the parameters from PBL, BPL and ML are pH (8.60, 7.67 and 6.76), temperature (29.30, 33.02 and 29.47 o C), chromium hexavalent (0.030, 0.007 and 0.020 mg/L), SS (101.7, 127.3 and 45.0 mg/L), BOD5 (106.70, 144.07 and 100.30 mg/L), COD (153.7, 1418.0 and 257.5 mg/L), BOD5 /COD (0.69, 0.09 and 0.39 mg/L), copper (0.24, 1.52 and 0.10 mg/L), lead (1.95, 0.75 and 0.13 mg/L) and cadmium (0.03, 0.001 and 0.003 mg/L), were recorded, respectively. The obtained results were compared to the standard limit under the Environmental Quality (Control of Pollution from Solid Waste Transfer Station and Landfill) Regulation 2009. The leachate quality from PBL has the highest range of heavy metals, followed by BPL and ML which is due to landfill age. However, BPL shows greater organic contaminants such as SS, BOD5 and COD which may be due to the absence of leachate aeration facilities at the landfill site compared to PBL and ML. A proper treatment strategy is crucial to reduce the pollutants before being discharged into the water bodies. Keywords: Leachate, Characteristics, Parameters